ANALISIS TINGKAT AKURASI PENETAPAN NILAI JUAL OBJEK PAJAK (NJOP) BUMI DENGAN MENGGUNAKAN METODE ASSESSMENT SALES RATIO DI KOTA BANDA ACEH - Nadia Hudja; Wida Fadhlia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study aims to determine the suitability of the Assesment Ratio (AR) in each subdistrict of Banda Aceh based on the regulations set by Directorat General of Taxes and to find out the existence of intervals for Tax Object Sales Value (NJOP) assignment in Banda Aceh based on the standards set by the International Association of Assessing Officers (IAAO) . The method used in this study is descriptive quantitative by testing ASR for ratio studies, measurement of central tendency, and measurement of variability. The results of this study showed that during the 3 research assessment ratios (AR) in each sub-district in the city of Banda Aceh, which consisted of 9 sub-districts all were below the standard recommended by the Director General of Taxes and the IAAO or under-assessment so that a reassessment was needed.